Analisis Pengelolaan Administrasi Keuangan Pada Kantor Camat Nelle Kabupaten Sikka - Maria Yulia Dua Pona; Magdalena Silawati Samosir; Imelda Virgula Wisang (Universitas Nusa Nipa Maumere, 2022)
The background of this study is the issues encountered by the Sub-district Government in managing financial administration. This study aimed to find out how the management of financial administration at the Nelle Sub-District Office of Sikka Regency. This descriptive qualitative study provided an overview of planning, budgeting, reporting, accountablility, and evaluation. The data relied on primary data obtained from observation, interviews, and secondary data. The informants of the study were the Head of the Sub-District and the Head of Finance and Treasurer. The results indicated that the management of financial administration at the Nelle Sub-District Office was not fully in accordance with Permendagri NO.77 of 2020, While the obstacles faced by the Nelle Sub-District Office were the level of time discipline and the lack of human resources in quantity. Hence, the planning and reporting of accountability for the implementation of programs were not optimal.